Professional assessment compared to patients' attitudes toward tooth replacement: a cross-sectional study - Haidar Alalawi; Hasan Alhumaily (BMC, 2023)
Abstract Background There is a difference between patient self-assessment and professional assessment of oral health needs; therefore, the aim of the study was to investigate patients' individual needs and awareness of replacing missing teeth with prostheses and then to compare this information with professionally assessed clinical prosthetic needs in the Eastern Province of Saudi Arabia. Methods This was a cross-sectional study conducted in the Eastern Province of Saudi Arabia. The study subjects were recruited from Imam Abdulrahman bin Faisal University in Dammam City, Primary Health Care Centers in Alhasa City and from health education campaigns in the same area. All the patients were provided with a questionnaire related to the effect of missing teeth and replacement options, then underwent a clinical examination performed by a well-trained investigator. Statistical analyses were performed using JMP data analysis software (JMP®, Version 16. SAS Institute Inc., Cary, NC, 1989-2021.) Results A total of 102 participants were included. Most of the participants (94.2%) reported their need to replace missing teeth. Most of the participants stated that losing teeth (teeth) affected their ability to chew food and their appearance (82.6% and 61.6%, respectively). Dental caries was the main reason behind teeth extraction in 77.9% of the study sample. Fixed partial prosthesis was the first treatment option preferred by 33.7%, followed by implant-supported prosthesis with 25.6% to replace the missing teeth. Only 3.5% of participants preferred not to restore the missing teeth. Professional screening showed that 48.8% of the participants had one missing anterior tooth or more, which dictates the need for esthetic restoration, and 58.1% of the participants had three missing posterior teeth or more, which dictates the need for functional restoration. Conclusions Patient knowledge and attitudes toward replacing missing teeth in terms of their functional and esthetic needs were variable among the population in comparison to the professional assessment of patient needs. Dentists plays a major role in raising the level of awareness about missing teeth replacement. The results of this study serve as baseline data for any related future studies.